¿How to understand the end of conflict? addressing a theoretical context from Zartman’s theory and a “Three-Dimensional” view - Cano-Holguín, Nelson; Jiménez-Osorio, Javier (EFIM Ediciones, 2021)
Based on the assumption that each armed conflict has different origins, the end of the conflict corresponds to a cessation of hostile activities and the beginning of a peace process. However, recognizing when the parties immersed in a conflict have the will to negotiate is a complex issue to understand. In this sense, this article addresses Zartman’s theory of maturation to increase the understanding of the elements necessary for the parties to come together and resolve their conflicts. The novelty of this article is that it complements such a theory with a three-dimensional vision of the end of the conflict, that is, military, political and economic dimensions. Based on a bibliographic review, the main conclusion is linked to the possibility of providing the understanding of conflicts with some arguments through the theory of Zartman’s ripening; however, this still has limitations in the sense that such a moment of ripening does not guarantee that the conflict will be solved, nor does it offer a look at it before reaching that moment, but it is possible to observe it only after it passes, giving rise to new investigations that go deeper into those gaps.